Diffusion study in bcc_A2 Fe-Mn-Si system: Experimental measurement and CALPHAD assessment. (March 2017) - Deng, Shuwen; Chen, Weimin; Zhong, Jing; Zhang, Lijun; Du, Yong; Chen, Li
Abstract: Based on the recently developed numerical inverse method, high-throughput measurement of the composition-dependent interdiffusivity matrices in the bcc_A2 Fe-Mn-Si alloys at 1173, 1273 and 1373 K was performed in the present work. To verify the reliability of the presently determined interdiffusivities, the ternary interdiffusivities evaluated by the traditional Matano-Kirkaldy method at the intersection points of the diffusion paths were employed to make a direct comparison. Subsequently, on the basis of the presently obtained interdiffusivities together with the thermodynamic descriptions for bcc_A2 phase in the Fe-Mn-Si system, atomic mobilities of Fe, Mn and Si in bcc_A2 Fe-Mn-Si alloys were assessed by means of DICTRA (DIffusion Controlled TRAnsformatim) software package. The comprehensive comparison between various calculated/model-predicted diffusion properties, including interdiffusivities, concentration profiles, interdiffusion fluxes and diffusion paths, and the experimental data indicates that most of the experimental data can be well produced by the presently obtained atomic mobilities. Moreover, the reliability of the present atomic mobilities was further validated by reproducing the experimental composition profiles which were not utilized in the assessment procedure. Highlights: Interdiffusivities in bcc_A2 Fe-Mn-Si alloys were efficiently measured. Errors were evaluated via a scientific method considering error propagation. Atomic mobilities of bcc_A2 phase in the Fe-Mn-Si system were critically assessed. Reliability of the obtained atomic mobilities was comprehensively verified.